Applicantion Model of Transparency and Accountability of Regional Government Financial Reporting: It’s Influence on the Level of Regional Government Corruption in Indonesia - Sam, Iskandar; Kusumastuti, Ratih; Misni Erwati (Asian Journal of Management Analytics, 2024)
This research aims to empirically analyze the influence of transparency and accountability of local government financial reports (LKPD) on the level of local government corruption. It is important to carry out this research to see that the unqualified opinion (WTP) given by the Financial Audit Agency (BPK) has increased which shows that the presentation of regional government financial reports (LKPD) is getting better, but cases of corruption in government institutions continue to increase every year. The population used in this research is the City/Regency Governments throughout Riau. The type of data used in this research is secondary data. The City Government (Pemkot) that was the sample in this study was selected based on certain criteria (purposive sampling) with the aim of obtaining a sample that met the specified criteria. There are 15 city/district governments in Riau that can be used as samples in this research. The methods used in analyzing this research data are descriptive statistical analysis and inferential statistical analysis. Data processing was carried out using the IBM Statistical Package for Social Science (SPSS) version 25 and Warp PLS application programs. The research results prove that accountability influences the regional corruption index; Transparency influences the regional corruption index. Increasing accountability and transparency in government governance is an important step in efforts to reduce corruption and improve the quality of government in the regions. Concrete actions such as improving financial reporting, strengthening supervision, and increasing public access to government information must be taken to achieve this goal.